Current state and some issues of countering illegal trafficking in goods in Ukraine - Lysenko, Volodymyr; Hribov, Mykhailo; Kovalenko, Valentyn; Makarenko, Nataliia; Rohatiuk, Ihor (Cuestiones Políticas, 2020)
The aim of the article is to investigate the current state of illegal merchandise trafficking in Ukraine, as well as the basic conditions that promote the spread of counterfeiting in this country together with the methods to counteract this phenomenon. The research methodology was chosen based on the purpose and objectives of the study, consequently, a set of methods and approaches to scientific knowledge were combined, of a general theoretical and special scientific nature. Everything indicates that Ukraine is one of the world leaders in the illicit production and distribution of software, intellectual property, etc., and this problem has not been a priority for the authorities for a long time. It is concluded that the basic conditions that promote the spread of counterfeiting in Ukraine are determined on the basis of the analysis of the activities of the police and supervisory authorities in the fight against illegal trafficking of goods. The most efficient methods are proposed to counteract the illegal traffic of goods, within the framework of the underground economy in Ukraine.